Analisis perbandingan metode pendeteksian kecurangan keuangan menggunakan Altman Z-Score, Beneish M-Score, dan Springate - Pertiwi, Jihan Citra; Oktavia, Reni; Amelia, Yunia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Financial statements are a reflection of the company's financial performance, which is prone to fraud. BUMN, as a company whose assets are owned by the state, will be vulnerable to fraud. Based on ICW data, there were 28 cases of BUMN corruption in 2020. Financial fraud that occurred in BUMN companies themselves came into the public spotlight, so it is necessary for the community, government, and companies to know from an early age whether the company is in good health or not. This study aims to see how the influence of the Altman z-score, the beneficial m-score, and the springate methods influence the detection of fraud tendencies that exist in companies and to see a comparison of the most appropriate methods to be used as predictors. This type of research is quantitative and uses secondary data sources. The samples used were from 16 companies for 5 years, with statistical analysis using the SmartPLS statistical application. The results of this study are the Altman z-score, Beneish m-score, and Springate methods. has a positive and insignificant effect on detecting financial fraud in state-owned companies during 2015–2020.